Facade Ornamentation as Resilience Strategy: Case Study of Regional Architectural Elements Application in Indonesian Government Buildings - Wahyu Hidayat; RA Retno Hastijanti; Darmansjah Tjahja Prakasa (International Conference of Innovation and Community Engagement, 2024)
This research examines the application of facade ornamentation as a resilience strategy in Indonesian government building architecture. The main focus is on how regional architectural elements are integrated into modern building facade designs to create sustainable cultural identity. Through a case study approach of several government buildings across different regions in Indonesia, this research analyzes the effectiveness of ornamentation in bridging tradition and modernity, as well as its ability to adapt to environmental and social changes. The research methodology employs visual theory and analysis. Results show that facade ornamentation, when designed with consideration of local context and sustainable design principles, can enhance building resilience both culturally and environmentally. This research contributes to understanding the role of ornamentation in contemporary Indonesian architecture and offers practical recommendations for designing government buildings that are responsive to local cultural heritage and modern demands.